2021
DOI: 10.1136/bmjgh-2021-005519
|View full text |Cite
|
Sign up to set email alerts
|

Lowering drug prices and enhancing pharmaceutical affordability: an analysis of the national volume-based procurement (NVBP) effect in China

Abstract: To cope with the increasing healthcare costs brought about by the universal health insurance programme, national volume-based procurement (NVBP) was implemented in China to reduce drug prices. However, the impact of NVBP remains unknown. We reported the effects of the NVBP pilot programme on medication affordability and discussed the challenges and recommendations for further reforms. A total of 25 molecules won the bidding in the NVBP pilot programme, and price cuts ranged from 25% to 96%. Medication affordab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 21 publications
1
85
0
Order By: Relevance
“…Volume-based drug procurement, also known as 'group purchasing', by integrating the procurement needs of all pilot cities, enhanced the negotiation power of hospitals and payers to maximise the price reduction of drugs. 10 Volume-price linkage was achieved under this procurement mechanism. 11 In the NCDP policy, only generic drugs that had previously passed the Generic Consistency Evaluation (GCE) and original branded drugs were eligible to be listed for procurement.…”
Section: Open Accessmentioning
confidence: 96%
See 3 more Smart Citations
“…Volume-based drug procurement, also known as 'group purchasing', by integrating the procurement needs of all pilot cities, enhanced the negotiation power of hospitals and payers to maximise the price reduction of drugs. 10 Volume-price linkage was achieved under this procurement mechanism. 11 In the NCDP policy, only generic drugs that had previously passed the Generic Consistency Evaluation (GCE) and original branded drugs were eligible to be listed for procurement.…”
Section: Open Accessmentioning
confidence: 96%
“…In the policy, unique measures, such as 'ensuring drug quality', 'achieving volume-price linkage' and 'encouraging generic substitution and rational use', were applied to achieve price cuts and improve medicine affordability with higher quality. [9][10][11] Twenty-five drugs in the '4+7' procurement list were successfully purchased with an average price reduction of 52%, of which 22 were generic drugs that passed the GCE and 3 were original drugs. 17 Worldwide, tendering for off-patent medicines and promoting generic substitution are effective ways to enhance market competition, which contribute to drug cost-containment.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of NCDP policy has achieved remarkable results in improving the accessibility of policy-related drugs [14][15][16], promoting the substitution use of generic drugs [17], and increasing overall drug use quality level of the public [18]. However, several previous studies reported an upward trend in the consumption of policy-related drugs after the implementation of NCDP policy [11,19], which should be concerned, especially for the incrased consumption of drugs have not been covered by NCDP policy.…”
Section: Introductionmentioning
confidence: 99%